2021
DOI: 10.1080/08959420.2021.1935144
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Policy Challenges and Strategies Supporting Informal Caregivers in the European Union

Abstract: Cost containment and the preferences of older adults are important stimuli for encouraging the provision of informal care worldwide. Nevertheless, informal caregiving can have negative effects on caregiver's health, wellbeing, and employment opportunities. Moreover, it is questionable whether informal caregivers can substantially contribute to meeting the increasing demand for care or serve as a substitute for formally provided services. This commentary assesses strategies to remediate the negative effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…A recent study found that the lack of supportive policies and actual support for informal carers within the European Union increases the negative consequences of informal care provision such as unemployment [ 69 ], while a recent European report concluded that better support and policies are needed for informal carers across the EU [ 18 ]. Sweden was one of the first countries to implement gender-equality policies, with policies such as individual income taxation, the development and expansion of public childcare, and access to gender neutral parental leave in place since the 1970s [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that the lack of supportive policies and actual support for informal carers within the European Union increases the negative consequences of informal care provision such as unemployment [ 69 ], while a recent European report concluded that better support and policies are needed for informal carers across the EU [ 18 ]. Sweden was one of the first countries to implement gender-equality policies, with policies such as individual income taxation, the development and expansion of public childcare, and access to gender neutral parental leave in place since the 1970s [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…But with population aging, changing family structures, and growing concerns about the economic cost of long-term residential care, the support of community-based informal caregivers has become a prominent policy topic. Concerns about whether countries will have resources to meet increasing demand for services for older persons focus on several societal developments (Wieczorek et al, 2021). These include increased labor force participation of women, changes in retirement policies and pension age, lower fertility rates, rising childlessness and higher divorce rates.…”
Section: Introductionmentioning
confidence: 99%
“…This is an important research and policy topic given the current drive by many Western governments to reconfigure services for care of older people by shifting the balance away from residential to community settings. Our construction of the framework has been shaped particularly by four seminal papers on caregiving, namely: the works of Twigg (1989), Cass and colleagues (Cass et al, 2014), the United Nations Economic Council for Europe Working Group on Aging (UNECE, 2019) and Wieczorek et al (2021). We use the framework to address the role of caregivers and in so doing touch on issues affecting care recipients.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, economic theories are used to examine predictors of sustained employment for caregivers, framing sustained employment as a choice based on an evaluation of advantages and disadvantages for the caregiver (Lilly et al, 2007; Miller & Sedai, 2022; Schmitz & Westphal, 2017). Lastly, studies focus on structural factors shaping the workplace environment, which include the broader social policy environment (i.e., laws protecting caregivers) as well as specific employment policies that can moderate the impact of workplace stressors on caregivers (Arksey & Glendinning, 2007; Pavalko & Henderson, 2006; Wieczorek et al, 2022).…”
Section: Discussionmentioning
confidence: 99%